SOSIALISASI PEMULIHAN EKONOMI PASCA PANDEMI COVID 19 MELALUI KEARIFAN LOKAL DI DESA RANOOHA RAYA KECAMATAN MORAMO KAABUPATEN KONAWE - Akhmad Marhadi; La Ino; La Ode Topo Jers; Erens Elvianus Koodoh; Maliudin Maliudin; Fina Amalia Masri (Jurnal Pengabdian NUSANTARA, 2022)
The implementation of this service aims to promote post-covid 19 recoveries through local wisdom which is located in Ranooha Raya Village, Moramo District, Kabupaten Konawe. This is based on the fact that after two consecutive years, Indonesia has been hit by the 2019 Covid-19 pandemic which has made all aspects of life, especially health and the economy, worse off. After redundant two years, the development of Covid 19 was increasingly sloping, so everyone started to clean up. The method used in this dedication is with several stages, namely the stages of preparation and debriefing, implementation of activities, and control. The results of the Thematic KKN integrated service activities are that the community produces handicrafts, does greenery, and socializes in schools about awareness of how to fill in various positive activities after the pandemic.